The long-term effects of interface irrigation on visual outcomes and corneal aberrations in Small Incision Lenticule Extraction (SMILE) - Sibel Ahmet; Murat Kocamaz; Cem Sarı; Ahmet Kırgız; Yusuf Yıldırım; Muhittin Taşkapılı (Indian Journal of Ophthalmology)
Purpose: To assess the long-term effects on visual outcomes and corneal aberrations of irrigating the interface during the small-incision lenticule extraction (SMILE) surgery for managing myopia and myopic astigmatism. Methods: In 47 patients who underwent bilateral SMILE surgery for myopia and myopic astigmatism, one eye was irrigated with 1.0 ml of balanced salt solution via cannula (Group 1) and the other eye was not irrigated (Group 2). Visual and refractive outcomes of 94 eyes were analyzed on the first day, first week, first month, sixth month, and first year. Preoperative and postoperative corneal higher-order aberrations (HOAs) obtained from Sirius corneal tomography (Costruzione Strumenti Oftalmici, Florence, Italy) were evaluated in both groups. Anterior segment optical coherence tomography (Heidelberg Spectralis; Heidelberg Engineering, Heidelberg, Germany) was used for interface evaluation on the first postoperative day. Intraoperative and postoperative complications were recorded. Results: Preoperative spherical, cylindrical, and spherical equivalent values were similar in both groups (P values: 0.913, 0.796, and 0.876, respectively). Statistically significant increases in mean HOAs and coma values were observed in both groups during the postoperative follow-up periods compared to the preoperative period (each P value <0.05). No significant differences were noted between the two groups concerning visual acuity, refractive values, and corneal aberrations throughout all postoperative follow-up periods (each P value >0.05). Epithelial inoculation developed in one eye in the irrigated group, and diffuse lamellar keratitis developed in one eye in the non-irrigated group. Conclusion: This study demonstrated that the visual, refractive, and wavefront aberration outcomes, both in the short and long term, were comparable between cases with and without interface irrigation following lenticule removal from the stromal pocket in SMILE surgery.